Exploring nutraceutical approaches linking metabolic syndrome and cognitive impairment - Rebecca Sonnino; Gea Ciccarelli; Simona Moffa; Laura Soldovieri; Gianfranco Di Giuseppe; Michela Brunetti; Francesca Cinti; Eleonora Di Piazza; Antonio Gasbarrini; Enrico C. Nista; Alfredo Pontecorvi; Andrea Giaccari; et al. (iScience)
Summary: Metabolic syndrome (MetS) and mild cognitive impairment (MCI) are interconnected conditions sharing common pathological pathways, such as inflammation and oxidative stress, leading to the concept of “metabolic-cognitive syndrome.” This highlights their mutual influence and potential overlapping therapeutic strategies. Although lifestyle modifications remain essential, nutraceutical supplementation has emerged as a promising adjunct for the prevention and management of these preclinical conditions. This review examines clinical and translational evidence on commonly used nutraceuticals targeting shared pathophysiological mechanisms of MetS and MCI. By addressing inflammation, oxidative stress, and metabolic dysfunction, these supplements may offer a valuable approach to mitigating the progression and consequences of both conditions. Understanding their efficacy could provide practical tools to complement lifestyle changes, offering a more comprehensive strategy for managing metabolic-cognitive syndrome.